The significance of biological samples from pregnant women in cervical intraepithelial neoplasia - Mi, Xue; Rashmi, Maharjan; Pan, Zangyu; Wu, Di; Miao, Jinwei (Frontiers in Medicine, 2025)
Background and aimsCervical cancer remains a significant threat to women’s health, with pregnant women representing a particularly vulnerable population. This study aimed to investigate the impact of cervical intraepithelial neoplasia (CIN) on pregnancy outcomes using longitudinal biological sample analysis.MethodsWe conducted a retrospective study of 125 pregnant women who underwent vaginal examination following abnormal cervical cytology and/or positive human papillomavirus (HPV) testing. Suspected cases underwent colposcopy-directed cervical biopsy performed by experienced clinicians (10 year of work experience) during pregnancy. Postpartum follow-up included repeat cervical cytology, HPV testing, and colposcopic biopsy when indicated.ResultsAmong the 125 patients, 34 underwent colposcopic biopsy during pregnancy, with histopathological results demonstrating strong concordance with colposcopic findings (kappa = 0.82, *p < 0.001). Postpartum follow-up within one year of delivery included colposcopy and cervical biopsy in 98 patients. Multivariate logistic regression analysis revealed that persistent cervical cytological abnormalities (OR 9.838; 95% CI 3.851–25.135; *p < 0.001) were significantly associated with abnormal colposcopic findings.ConclusionFor pregnant women declining cervical biopsy during pregnancy, colposcopy represents a safe and clinically valuable diagnostic tool. Persistent cervical cytological abnormalities, but not HPV positivity, were identified as a significant risk factor for CIN2 + persistence.